CHANGING PROFILE OF ENTERIC FEVER IN CHILDREN
A total of 300 cases of PUO (Pyrexia of Unknown Origin) were admitted to the Paediatrics Unit of Women and Children Hospital, Abbottabad during one year (June 1994 - May, 1995). They were examined for their detailed clinical profile. About 2/3rd of them had fever as their presenting symptom. Other associated predominant features were dizziness-51 (30%), anorexia-48 (28%), loose motions-47 (27.6%), cough-38 (22.4%